Technologizing of Georgian Language/the Most Urgent Tasks/ - Putkaradze, Tariel (Actual Problems of Kartvelology, 2013)
In order to leave the Georgian literary language among the world’s cultural languages in the condition of the contemporary or future technological leaps, it is necessary to put the automatic translation of the written and later oral texts into practice; this will enable Georgian citizens to get the information presented in the global network in their native tongue. State language is the standard for measuring the dignity of the nation, the level of technologizing of the state language is the standard of measurement of any modern state; besides, only turning Georgian into the language of modern technologies will preserve mother tongue- the defining phenomenon of the Georgian national identity; therefore, together with the automatized translation, it is necessary to prepare computer programs which will ensure the fullscale technologizing of the Georgian language